2009
DOI: 10.1038/oby.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake‐independent Effects of CB1 Antagonism on Glucose and Lipid Metabolism

Abstract: Overactivity of the endocannabinoid system (ECS) has been linked to abdominal obesity and other risk factors for cardiovascular disease and type 2 diabetes. Conversely, administration of cannabinoid receptor type 1 (CB1) antagonists reduces adiposity in obese animals and humans. This effect is only in part secondary to the anorectic action of CB1 agonists. In order to assess the actions of CB1 antagonism on glucose homeostasis, diet‐induced obese (DIO) rats received the CB1 antagonist rimonabant (10 mg/kg, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
5
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 24 publications
9
54
5
2
Order By: Relevance
“…Our findings are consistent with accumulating evidence suggesting that part of the metabolic effect of chronic CB1R antagonists is independent of reduction in energy intake, pointing to a role for peripheral tissue CB1R in induction of weight loss. In humans [43] and animal models [10,[12][13][14][15][16], changes in body weight during CB1R agonist or antagonist treatments can be independent of food intake, suggesting that CB1R plays a role in directly mediating metabolism. In accordance with our finding that CB1R mediates muscle insulin sensitivity, the role of CB1R in mediating energy expenditure has previously been shown to occur in peripheral tissues, by which mechanism a non-brain-penetrant CB1R antagonist reduced body weight and improved metabolism in mice [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with accumulating evidence suggesting that part of the metabolic effect of chronic CB1R antagonists is independent of reduction in energy intake, pointing to a role for peripheral tissue CB1R in induction of weight loss. In humans [43] and animal models [10,[12][13][14][15][16], changes in body weight during CB1R agonist or antagonist treatments can be independent of food intake, suggesting that CB1R plays a role in directly mediating metabolism. In accordance with our finding that CB1R mediates muscle insulin sensitivity, the role of CB1R in mediating energy expenditure has previously been shown to occur in peripheral tissues, by which mechanism a non-brain-penetrant CB1R antagonist reduced body weight and improved metabolism in mice [44].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight reductions through CB1R antagonism can only partially be explained by reductions in food intake; moreover, a variety of metabolic benefits of CB1R antagonism occur independently of reductions in energy intake [7,[12][13][14], suggesting that peripheral tissue CB1R plays a role in inducing weight loss. In diet-induced obesity, chronic CB1R antagonism causes weight loss and improves insulin sensitivity by diverting lipids from storage toward utilisation, a process that occurs independently of food intake [15]. Whole-body Cb1r (also known as Cnr1) knockout (Cb1r −/− ) mice are resistant to dietinduced obesity, while wild-type littermates on the same diet with identical energy intake become obese [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, much evidence with herbal cannabinoids, endogenous cannabinoids, cannabinoid receptor knockout animals, and cannabinoid receptor antagonists has demonstrated a complex interplay of mechanisms for controlling eating behaviors and regulating energy metabolism that involve both central and peripheral mechanisms (Di Marzo and Matias, 2005;Pagotto et al, 2006;Kunos et al, 2008;Nogueiras et al, 2008Nogueiras et al, , 2009Osei-Hyiaman et al, 2008;Cota et al, 2009;Quarta et al, 2010). Indeed, the brain endocannabinoid system controls food intake at two levels; it tonically reinforces the motivation to find and consume foods with a high incentive value by interacting with mesolimbic pathways involved in reward mechanisms, and it is activated on demand in the hypothalamus after short-term food deprivation and transiently regulates action of other orexigenic and anorectic mediators to induce appetite (Di Marzo and Matias, 2005;Pagotto et al, 2006;Quarta et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian endocannabinoid system has been extensively characterized over the last 20 years and is now known to play a key role in energy homeostasis by modulating both food intake and peripheral energy metabolism (Pagotto et al, 2006;Nogueiras et al, 2008Nogueiras et al, , 2009Osei-Hyiaman et al, 2008;Cota et al, 2009;Quarta et al, 2010). In general, stimulation of the endocannabinoid system influences metabolic pathways that lead to weight gain, lipogenesis, and impaired glycemic control (Hao et al, 2000;Bensaid et al, 2003;Engeli et al, 2005;Jbilo et al, 2005;Poirier et al, 2005;Matias et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…164 The endocannabinoid system plays a key role in energy homeostasis by modulating both food intake and energy expenditure. [165][166][167][168][169][170] Cannabinoid 1 (CB 1 ) receptor antagonists exhibit pharmacological properties favorable to treatment of obesity and diabetes, 171,172 but the relative contribution of their effects on appetite and energy expenditure are uncertain and difficult to assess clinically. Studies evaluating the CB 1 receptor antagonist, PF-95453, in obese, insulin-resistant cynomolgus macaques demonstrated that, as in humans, the effects of CB 1 receptor blockade on energy metabolism in monkeys involve both drugdependent reductions in food intake and food intakeindependent effects on energy expenditure.…”
Section: Pharmacologic Interventions In Nonhuman Primatesmentioning
confidence: 99%